Jurnal rekayasa proses - Universitas Gadjah Mada. Jurusan Teknik Kimia (Chemical Engineering Department, Faculty of Engineering, Universitas Gadjah Mada, 2007)
Current topics related to chemical and biochemical process exploration and optimization which covers multi scale analysis from micro to macro and full plant size.
Keywords: Chemical engineering : Periodicals; Chemical engineering : Indonesia : Periodicals; Chemical engineering; Indonesia